2019
DOI: 10.3390/su11236624
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of the Ecological Restoration of Quarry Slopes in Caidian District, Wuhan City

Abstract: Many measures have been applied to quarry slopes for ecological restoration; however, the performance of these measures has not been clearly evaluated. Thus, research evaluating the effects of the ecological restoration of quarry slopes in Caidian District was carried out to quantify the performance of different ecological restoration methods, to evaluate the effect of ecological restoration projects and to learn the applicability of different restoration technologies in Caidian District. The research can prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…According to the evaluation grade standard of the slope ecological restoration (Table4), and the original data of the seven cases (Table5) (Yang et al 2019), an Excel spreadsheet is set up to perform this method, as shown in Fig 2 . Enter the Eq. ( 1) into the spreadsheet columns labeled Similarity Measurement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the evaluation grade standard of the slope ecological restoration (Table4), and the original data of the seven cases (Table5) (Yang et al 2019), an Excel spreadsheet is set up to perform this method, as shown in Fig 2 . Enter the Eq. ( 1) into the spreadsheet columns labeled Similarity Measurement.…”
Section: Resultsmentioning
confidence: 99%
“…The selection of evaluation index of slope ecological restoration should reflect the effect of slope restoration systematically. On the basis of the existing research literature (Yang et al 2019;Carabassa et al 2019), this study combined with the actual situation to establish a comprehensive evaluation index system from the four aspects of substrate improvement effect, ecological effect, soil and water conservation effect and landscape effect.…”
Section: 2establishment Of the Evaluation Index Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…RTK, and the aerial survey which was carried out with the help of drones was used to locate the sample plot and the site factors such as aspects of the slope like slope length and soil thickness was investigated. The characteristics of the ecological restoration technology in the sample plot, in addition to the size and number of eroded ditches, were determined(Tian, 2011; Yang et al . , 2019).…”
Section: Methodsmentioning
confidence: 99%
“…As the emphasis for cut‐slope rehabilitation usually improves revegetation and soil erosion control, inorganic fertilizer is added to the sprayed artificial soil, so that a vegetation cover will be established in a short time (Chen et al, 2014; Yang et al, 2019). The soil nutrient status can have a direct impact on the success and speed of rehabilitation of cut slopes (Vitousek et al, 2010).…”
Section: Introductionmentioning
confidence: 99%